Brazilian Amazon indigenous lands: environmental threats, vulnerability, and public policies - Ana Claudia Rorato Vitor (2021)
Amazonian Indigenous Lands (ILs) are currently a worrying case of a vulnerable human-environmental system due to the environmental threats they have been suffering. The focus of this study is on how the different environmental threats affect the Amazonian Indigenous Lands, internally and externally, and how they influence the environmental vulnerability of these territories. In addition, given the strong importance of mining as an environmental threat, we assessed the extent of the potential impact of passing the proposed mining bill (PL 191/2020). Linked to these objectives, we discussed public policies as tools to reduce environmental threats in the ILs and to improve indigenous capacity to deal with them. For this, we explored three different approaches based on indicators as proxies of the threats and adaptive capacities: 1) grouping ILs according to the similarities found in the set of threat indicators within and around their limits through cluster analysis technique; 2) estimating the area of ILs covered by mining requests; 3) developing an environmental vulnerability assessment of Amazonian ILs by adopting the theoretical vulnerability framework of the IPCC. Most of the 383 Amazonian ILs are affected internally by a combination of different environmental threats. The set of threats in the ILs surroundings are very similar to the set of threats that affect Indigenous Lands internally, but the severity is generally higher. The ILs most affected by multiple and relatively severe threats are located mainly in the arc of deforestation and in the Roraima state. We have identified seven IL clusters with common environmental threats within and around their limits. Regarding the mining threat, we found that the existing mining requests cover 176,000 km2 of Amazonian ILs, most of them for gold exploration (64%), a factor 3000 more than the area of current illegal mining. In sum, about 15% of the total area of ILs in the region could be potentially affected by mining, if the mentioned bill is approved. The ethnic groups Yudjá, Kayapó, Apalaí, Wayana, and Katuena would even have between 47% and 87% of their lands impacted. Regarding the environmental vulnerability of Amazonian Indigenous Lands, in general, ILs with elevated Vulnerability are most concentrated in the arc of deforestation region and below, but also advancing to the inner of the Pará, Amazonas, and Roraima states. Our results also indicated an increase in Exposure (threats in ILs buffer zones), around 73.9%, and in Sensitivity (threats within IL), around 64.8%, of Amazonian ILs between 2011-2019 compared to 2001-2010, indicating a growing trend of the ILs vulnerability. Based on the results, we suggest four environmental policy priorities to be strengthened and applied in Amazonian ILs: protect ILs buffer zones; strengthen surveillance actions, and combat illegal deforestation, forest degradation, and mining activities in ILs; prevent and fight fires; and extrude invaders from ILs. In addition, it is essential to not approve predatory activities in ILs, such as mining. The obligation of the State is to enforce existing laws and regulations that put indigenous peoples rights and livelihoods above economic consideration and not to reduce such protections.